2016
DOI: 10.4103/1008-682x.155539
|View full text |Cite
|
Sign up to set email alerts
|

Acquired premature ejaculation and male accessory gland infection: relevance of ultrasound examination

Abstract: We have previously demonstrated a high frequency of premature ejaculation (PE) among patients with male accessory gland infection (MAGI). The aim of this study was to evaluate the ultrasound (US) features of patients with MAGI and acquired premature ejaculation (APE) associated (MAGI-APEpos). US evaluation of 50 MAGI-APEpos patients compared to 50 patients with MAGI without PE (MAGI-PEneg) which represent the control group. The diagnosis of APE was made through the evaluation of Intravaginal ejaculation latenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…A recent study demonstrated that in patients with male accessory gland infection (MAGI), patients with PE showed a mean value of the SVs APD detected before ejaculation, which was significantly higher compared to those without PE. 29 These results here represented the higher mean APD of SV in the patients with PE compared to healthy volunteers and confirmed that the peculiar ultrasound phenotype of SV may be associated with PE. In addition, these results revealed a positive linear relationship between PEDT score and the APD of SV, which was consistent with their results despite the difference in the correlation coefficient.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A recent study demonstrated that in patients with male accessory gland infection (MAGI), patients with PE showed a mean value of the SVs APD detected before ejaculation, which was significantly higher compared to those without PE. 29 These results here represented the higher mean APD of SV in the patients with PE compared to healthy volunteers and confirmed that the peculiar ultrasound phenotype of SV may be associated with PE. In addition, these results revealed a positive linear relationship between PEDT score and the APD of SV, which was consistent with their results despite the difference in the correlation coefficient.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, these results revealed a positive linear relationship between PEDT score and the APD of SV, which was consistent with their results despite the difference in the correlation coefficient. 29 Thus, the ultrasound change in SV is possibly associated with PE.…”
Section: Discussionmentioning
confidence: 99%
“…These forms differently impact sperm quality, sometimes irreversibly [19]. They also may contribute to sexual dysfunction, such premature ejaculation [31].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of patients with MAGI (male accessory gland inflammation) could be very heterogeneous; in fact, these patients may require andrological evaluation for problems (male infertility) [ 1 , 2 ] and/or symptoms (chronic pelvic pain, ejaculatory and urinary disorders, and sexual dysfunction) [ 3 ]. Previously, we have shown that in the clinical practice, the use of a specific questionnaire [SI-MAGI (Structured Interview about Male Accessory Gland Inflammation)] helps to discriminate the differential diagnosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%